2017
DOI: 10.1111/ajfs.12174
|View full text |Cite
|
Sign up to set email alerts
|

How Does CEO Age Affect Firm Risk?

Abstract: Previous research demonstrates that older CEOs are associated with lower firm equity risk and fewer R&D expenditures. We examine the risk-taking behavior of CEOs and find that not only do older CEOs invest in less R&D, they do so sub-optimally, in the sense that CEO age distorts the effect of q on R&D investment decisions. We find that it is specifically through the channel of R&D investment that CEO age is associated with the reduction in firm equity risk. Consistent with the sub-optimality of these distortio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 55 publications
1
18
0
Order By: Relevance
“…The second instrumental variable is the current age of the CEO. Prior research has shown that older CEOs are more risk averse and are less likely to invest in R&D (Chowdhury & Fink, ; Kalyta, ), which is critical to support a prospector strategy. Our use of this instrument stems from the likely role of the firm's top decision makers, who serve as the primary link between the organization and its environment, in setting business strategy (Miles & Snow, ).…”
Section: Empiricial Resultsmentioning
confidence: 99%
“…The second instrumental variable is the current age of the CEO. Prior research has shown that older CEOs are more risk averse and are less likely to invest in R&D (Chowdhury & Fink, ; Kalyta, ), which is critical to support a prospector strategy. Our use of this instrument stems from the likely role of the firm's top decision makers, who serve as the primary link between the organization and its environment, in setting business strategy (Miles & Snow, ).…”
Section: Empiricial Resultsmentioning
confidence: 99%
“…Literature shows inconclusive results about the age and corporate performance relationship. For instance, some studies documented that younger CEOs invest more in R&D (Barker and Mueller, 2002; Chowdhury and Fink, 2017; Gan, 2019) and have more volatile earnings than older ones (Zhou and Wang, 2014). This means that firms with younger CEOs are relatively more exposed to risk and are susceptible to investment inefficiency.…”
Section: Literature and Hypothesis Developmentmentioning
confidence: 99%
“…As growing old, top executives, including CEOs, are inclined to become more conservative, reputation-concerned and risk-averse (Chowdhury & Fink, 2017;Maccrimmon & Wehrung, 1990). CEOs' preference for the quiet life increases with age, which means that older CEOs would be unwilling to initiate risky move or intentionally defend against potential risks.…”
Section: The Moderating Effect Of Ceo's Agementioning
confidence: 99%